Study on educational leadership in the directors of the Julio María Matovelle Educational Unit of Puerto Bolívar - VELAZQUEZ CORDOVA, BERTHA YOLANDA; Gómez Hurtado, Inmaculada (Revista Ecos de la Academia, 2022)
The present study seeks to reveal the existing interrelationships between directors, teachers, students, and representatives of the Julio Matovelle Educational Unit of the Puerto Bolívar parish, Machala Canton, where it has been observed that these are influenced by the type of leadership of the scholar management. The research was carried out with a quantitative methodology for the analysis of data on behaviors and opinions of directors, teachers, parents, and students, through the Vanderbilt questionnaire adapted to Spanish on educational leadership. In the results, it is observed that the criteria of teachers and administrators on the quality of teaching, the culture of learning, and professional work differ with respect to those expressed by students and parents, while with respect to the relationship with the community there are matches. It has been concluded that managers tend to assume educational management as their own responsibility, where sometimes the criteria and needs of the students are not included, while on the part of the parents there is confidence in what the institution can do. for the education of their children, however, there are unsatisfied needs that do not have spaces for approach and dialogue to be exposed or solved.